PENALTIES FOR VIOLATION OF THE TAX LEGISLATION - Marina Kobylatova; Elena Kusch (Вестник Северо-Кавказского федерального университета)
Tax offenses are a threat to society, because their growth decreases the ability of the state to make rational use of financial resources and provokes a relative instability in the economy and politics. Tax law in regulating social relations that arise in the process ofpaying taxes, and in the formation of the rights and duties of subjects of tax relations uses various measures of state coercion, when the revealed violations by entities of their responsibilities. Due to the fact that sanctions for tax offences are proprietary in nature, it is essential to solve issues of economic feasibility for their establishment.